2023
DOI: 10.1029/2022wr033342
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Quantify Irrigation Water‐Use by Assimilating a High‐Resolution Satellite Soil Moisture Product?

Abstract: Agricultural production is projected to require a 70% expansion by 2050 as a result of population growth, climate change, and dietary shifts toward water-intensive products associated with increasing incomes (Tilman & Clark., 2015). Food production is mainly sustained by irrigation (Jägermeyr et al., 2015), which is by far the largest consumer of freshwater resources globally (Döll & Siebert, 2002). However, the planetary limit for freshwater withdrawal is quickly approaching (or already exceeded) in many part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 107 publications
(191 reference statements)
0
5
0
Order By: Relevance
“…The failure of S1-B halved the number of available observations (one every ∼4 days in Europe, 12 days elsewhere), making the buddy check approach (used within a S1 DA system) unsuitable outside of Europe until the launch of the next satellite (S1-C, expected in the near future). Other synthetic studies assimilating S1-related SSM products (Abolafia-Rosenzweig et al, 2019;Jalilvand et al, 2023;Ouaadi et al, 2021;Zappa et al, 2022) also highlighted the importance of frequent observations. Zappa et al (2022) reported large irrigation underestimations when observations are too sparse in time.…”
Section: Novel Approach To Estimate Irrigation In a Da Systemmentioning
confidence: 97%
See 1 more Smart Citation
“…The failure of S1-B halved the number of available observations (one every ∼4 days in Europe, 12 days elsewhere), making the buddy check approach (used within a S1 DA system) unsuitable outside of Europe until the launch of the next satellite (S1-C, expected in the near future). Other synthetic studies assimilating S1-related SSM products (Abolafia-Rosenzweig et al, 2019;Jalilvand et al, 2023;Ouaadi et al, 2021;Zappa et al, 2022) also highlighted the importance of frequent observations. Zappa et al (2022) reported large irrigation underestimations when observations are too sparse in time.…”
Section: Novel Approach To Estimate Irrigation In a Da Systemmentioning
confidence: 97%
“…Abolafia-Rosenzweig et al ( 2019) performed SMAP SSM DA into the variable infiltration capacity (VIC) LSM, using a particle batch smoother. With the intent of going to a finer resolution, Jalilvand et al (2023) used a similar approach using the S1-SMAP SSM product (Das et al, 2019). Ouaadi et al (2021) assimilated S1-derived SSM data into the FAO-56 (Allen et al, 1998) model with a particle filter.…”
Section: Introductionmentioning
confidence: 99%
“…The third group of approaches estimates irrigation amounts directly by assimilating SM observations into Land Surface Models and simulating irrigation events with this information [39][40][41]. Even if quite robust and accurate, LSMs often require many inputs to completely simulate the plant and soil at each step, and extensive calibration, reducing the possibility of large-scale operationalization of the approach.…”
Section: Introductionmentioning
confidence: 99%
“…They also highlighted the importance of tackling the issue of persistent biases between simulated and observed SSM. Jalilvand et al (2023) applied the same approach but using the 1 km resolution SMAP-S1 SSM data (Das et al, 2019) over an irrigation district in Iran. They confirmed the importance of an a priori knowledge of irrigation frequencies in their approach and obtained an underestimation of seasonal cumulative irrigation at the irrigated pixels by an average of 19%, explained by the loss of irrigation signal due to the mismatch between the spatial resolution (1 km) of SSM data and the scale of irrigation practices.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach has the disadvantage of potentially deleting signals when the observations contain some information that is not modeled, such as irrigation (Kumar et al, 2015;Nair and Indu, 2019). Another way to minimize such a bias is to calibrate model parameters on rainfed pixels (e.g., Dari et al, 2020Dari et al, , 2022Jalilvand et al, 2023), although this implies the strong (and unverified) assumption that optimal parameters for rainfed pixels are also optimal for irrigated pixels. Another approach is to remove a systematic bias (calculated on rainfed pixels) from the simulated irrigations (Jalilvand et al, 2019), although part of the signal may be lost due to the difference in climatology or soil properties between both pixel types (Brombacher et al, 2022).…”
Section: Introductionmentioning
confidence: 99%